1997 Proceedings 47th Electronic Components and Technology Conference
DOI: 10.1109/ectc.1997.606299
|View full text |Cite
|
Sign up to set email alerts
|

Influence of preheat and maximum temperature of the solder-reflow profile on moisture sensitive IC's

Abstract: The purpose of this work was to determine the influence of preheat and maximum solder reflow temperature on the level of moisture induced damage in plastic surface mount integrated circuits. Both an analytical moisture diffusion model and Finite Element Modeling were applied to the analysis of absorption/desorption behavior of plastic molding compounds. The models were used to analyze the moisture ingress kinetics during controlled environmental exposures and for the prediction of moisture desorption character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Equation (1) will be used in Section III for temperatures up to 215 C. This extrapolation is allowed, as can be concluded from [12]. The values for the diffusivity coefficients and activation Table I.…”
Section: B Moisture Diffusivities and Saturation Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (1) will be used in Section III for temperatures up to 215 C. This extrapolation is allowed, as can be concluded from [12]. The values for the diffusivity coefficients and activation Table I.…”
Section: B Moisture Diffusivities and Saturation Concentrationsmentioning
confidence: 99%
“…It was assumed that moisture transport occurred only by diffusion and the corresponding diffusivity, therefore, was calculated as shown for example in [11]. The temperature dependence of the diffusivity was modeled by an Arrhenius equation [10], [12] (1)…”
Section: B Moisture Diffusivities and Saturation Concentrationsmentioning
confidence: 99%
“…R.L. Shook (1997) [2] and Yizhe Elisa Huang (1998) [3] applied these on plastic package delamination with the existence of moisture. Zhenwei Hou (2001) [4] and Chunyan Yin (2004) [5] investigated the Effects of Solder Reflow on the Reliability of Flip-Chip.…”
Section: Introductionmentioning
confidence: 98%
“…It can be easily shown that a plot of In(D) vs liT will he a straight line. Figure 5 plots In(D) versus (UT) as obtained by Kitano [3] and Shook [6] at various temperatures. It can he seen that at 0°C there is ahout a 14X difference in diffusivity value as found by Kitano [31 and that by Shook [61. Obviously they looked at different mold compounds.…”
Section: Scalability With Thichessmentioning
confidence: 98%
“…Certainly IC manufacturers and users would want to see the same popcorn jeopardy threshold in any given level for disparate packages. Some elemem of the current proposed approach have been implemented and discussed by several authors [1][2][3][4][5][6][7][8][9]. The novelty of the current proposal is in the total approach and a methodology to design 'levels' taking into account the physics of moisture absorption.…”
Section: A Computer-based Trackingmentioning
confidence: 99%